Role and Level of E-CRM in Women-Headed Micro, Small, and Medium Enterprises in Sri Lanka - Sathana, V. (University of Jaffna, 2024)
Purpose: Women in the SME sector play a prominent role in the development of Sri Lanka; at the same time, they have been facing huge problems and challenges to sustain in the environment. The purpose of this research is to find out the level and role of e-CRM application in women-headed SMEs in Sri Lanka. Design/Methodology/Approach: The researcher applied a quantitative study in this research; the respondents are the female owners of MSMEs, convenient sampling techniques were applied to select the respondents, and data were collected from 284 respondents by using structured questionnaires. Data was analyzed by using descriptive statistics based on the type and nature of the MSMEs. Findings: The roles of e-CRM were explained by two dimensions customer communication and customer information management. Under the role of e-CRM, regarding the integration of communication channels, SMEs moderately accept the internet communication key to business and internet-based technologies have improved communication. Regarding the level of e-CRM, SMEs are moderately using the Internet and more than 60 percent of businesses are initiated by the Internet whereas they failed to update their website weekly and integrate Internet technology. Research limitations: SMEs are using e-CRM on an ad-hoc basis and those are strategically utilizing e-CRM who are reaping significantly greater benefits and fewer challenges. Research should be conducted to identify the depth roles and level of e-CRM on the specific nature of SMEs Implications: this finding reveals that SMEs need to update websites frequently, are more in complete integration of internet technologies in their firms and have more concern on e-CRM to develop their business. Owners of small businesses and manufacturing firms need to realize that Internet communication is key to business. Small and manufacturing firms need to understand that electronic communication is proactively used to develop customer relationships.
Keywords: Electronic Customer Relationship Management; Women-headed SMEs; Integration of communication channels; Information management integration